Suturable regenerated silk fibroin scaffold reinforced with 3D-printed polycaprolactone mesh: biomechanical performance and subcutaneous implantation - Cengiz, I. F. (2019)
The menisci have crucial roles in the knee, chondroprotection being the primary. Meniscus repair or substitution is favored in the clinical management of the meniscus lesions with given indications. The outstanding challenges with the meniscal scaffolds include the required biomechanical behavior and features. Suturability is one of the prerequisites for both implantation and implant survival. Therefore, we proposed herein a novel highly interconnected suturable porous scaffolds from regenerated silk fibroin that is reinforced with 3D-printed polycaprolactone (PCL) mesh in the middle, on the transverse plane to enhance the suture-holding capacity. Results showed that the reinforcement of the silk fibroin scaffolds with the PCL mesh increased the suture retention strength up to 400%, with a decrease in the mean porosity and an increase in crystallinity from 51.9 to 55.6%. The wet compression modulus values were significantly different for silk fibroin, and silk fibroin + PCL mesh by being 0.16 Â± 0.02, and 0.40 Â± 0.06 MPa, respectively. Both scaffolds had excellent interconnectivity (>99%), and a high water uptake feature (>500%). The tissueâ s infiltration and formation of new blood vessels were assessed by means of performing an in vivo subcutaneous implantation of the silk fibroin + PCL mesh scaffolds that were seeded with primary human meniscocytes or stem cells. Regarding suturability and in vivo biocompatibility, the findings of this study indicate that the silk fibroin + PCL mesh scaffolds are suitable for further studies to be carried out for meniscus tissue engineering applications such as the studies involving orthotopic meniscal models and fabrication of patient-specific implants.